Reciprocal interactions of bone marrow-derived mesenchymal stem cells and BV2 microglia following lipopolysaccharide stimulation - Rahmat, Zul'atfi; Jose, Shinsmon; Ramasamy, Rajesh; Vidyadaran, Sharmili (BioMed Central, 2013)
INTRODUCTION: Mesenchymal stem cells (MSCs) are immunosuppressive, but we lack an understanding of how these adult stem cells are in turn affected by immune cells and the surrounding tissue environment. As MSCs have stromal functions and exhibit great plasticity, the influence of an inflamed microenvironment on their responses is important to determine. MSCs downregulate microglial inflammatory responses, and here we describe the mutual effects of coculturing mouse bone marrow MSCs with BV2 microglia in a lipopolysaccharide (LPS) inflammatory paradigm. METHODS: Mouse MSCs were cultured from femoral and tibial bone marrow aspirates and characterized. MSCs were cocultured with BV2 microglia at four seeding-density ratios (1:0.2, 1:0.1, 1:0.02, and 1:0.01 (BV2/MSC)), and stimulated with 1 μg/ml LPS. In certain assays, MSCs were separated from BV2 cells with a cell-culture insert to determine the influence of soluble factors on downstream responses. Inflammatory mediators including nitric oxide (NO), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and chemokine (C-C motif) ligand 2 (CCL2) were measured in cocultures, and MSC and BV2 chemotactic ability determined by migration assays. RESULTS: We demonstrated MSCs to increase expression of NO and IL-6 and decrease TNF-α in LPS-treated cocultures. These effects are differentially mediated by soluble factors and cell-to-cell contact. In response to an LPS stimulus, MSCs display distinct behaviors, including expressing IL-6 and very high levels of the chemokine CCL2. Microglia increase their migration almost fourfold in the presence of LPS, and interestingly, MSCs provide an equal impetus for microglia locomotion. MSCs do not migrate toward LPS but migrate toward microglia, with their chemotaxis increasing when microglia are activated. Similarly, MSCs do not produce NO when exposed to LPS, but secrete large amounts when exposed to soluble factors from activated microglia. This demonstrates that certain phenotypic changes of MSCs are governed by inflammatory microglia, and not by the inflammatory stimulus. Nonetheless, LPS appears to "prime" the NO-secretory effects of MSCs, as prior treatment with LPS triggers a bigger NO response from MSCs after exposure to microglial soluble factors. CONCLUSIONS: These effects demonstrate the multifaceted and reciprocal interactions of MSCs and microglia within an inflammatory milieu.